2020
DOI: 10.1148/radiol.2020200225
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Spin Labeling MRI in Carotid Stenosis: Arterial Transit Artifacts May Predict Symptoms

Abstract: Artifact (ATA) was present in 16/16 participants with severe stenosis (>70%), p <.001), and were associated with absence of anterior communicating artery (11/16, p=.003). ATA was the best predictor of recent symptoms in internal carotid artery stenosis (13/16 participants with ATA had symptoms, p=004).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 38 publications
(46 reference statements)
0
18
0
Order By: Relevance
“…Later study revealed that vessel‐encoded arterial spin labeling (VEPCASL) could achieve collateral perfusion and delayed blood arrival information noninvasively and serially in AIS patients, which information was proved to be related to tissue survival 26 . In previous studies, ATA in ASL images has been proved to be associated with recent ischemic symptoms in patients with carotid stenosis 8 . Notably, ATA can attenuate the association between ASL perfusion defects and ipsilateral early ischemic recurrence in patients with DWI‐negative transient ischemic attacks 6 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Later study revealed that vessel‐encoded arterial spin labeling (VEPCASL) could achieve collateral perfusion and delayed blood arrival information noninvasively and serially in AIS patients, which information was proved to be related to tissue survival 26 . In previous studies, ATA in ASL images has been proved to be associated with recent ischemic symptoms in patients with carotid stenosis 8 . Notably, ATA can attenuate the association between ASL perfusion defects and ipsilateral early ischemic recurrence in patients with DWI‐negative transient ischemic attacks 6 .…”
Section: Discussionmentioning
confidence: 99%
“…26 In previous studies, ATA in ASL images has been proved to be associated with recent ischemic symptoms in patients with carotid stenosis. 8 Notably, ATA can attenuate the association between ASL perfusion defects and ipsilateral early ischemic recurrence in patients with DWI-negative transient ischemic attacks. 6 In recent study, the presence of collaterals blood vessels, defined as ATA in ASL images, was observed to be associated with admission NIHSS score and lower median mRS scores at discharge.…”
Section: Ta B L E 3 Performance Of Classifiersmentioning
confidence: 99%
See 2 more Smart Citations
“…An incomplete circle of Willis was defined if any of the three arterial segments was absent or hypoplastic (<0.8 mm in diameter) ( 27 ). Since the presence of posterior communicating artery had little effect on cerebral hemodynamics and clinical symptoms ( 28 ), posterior circulation arterial segments were not included.…”
Section: Methodsmentioning
confidence: 99%